Open Governance: A New Paradigm for Understanding Urban Governance in an Information Age - Meijer, Albert Jacob; Lips, Miriam; Chen, Kaiping (Frontiers in Sustainable Cities, 2019)
This theoretical viewpoint paper presents a new perspective on urban governance in an information age. Smart city governance is not only about technology but also about re-organizing collaboration between a variety of actors. The introduction of new tools for open collaboration in the public domain is rapidly changing the way collaborative action is organized. These technologies reduce the transaction costs for massive collaboration dramatically and thus facilitate new forms of collaboration that we could call ‘open governance’: new innovative forms of collective action aimed at solving complex public policy issues, contributing to public knowledge, or replacing traditional forms of public service provision. These innovative open and collaborative organisational forms in cities seem to point towards not only a wide variety of digitally connected actors but also to a fundamentally different and more invisible role of government in these arrangements. We argue that the recently emerging paradigm of New Public Governance (NPG) (Osborne 2010) also fails to capture the dynamics of open governance since it does not acknowledge the emergent – pop-up – character of the new collaborations; neither does it present an understanding of massive individualized collaboration in cities. This paper aims to theoretically and empirically explore the core elements and the underlying socio-technical developments of this new Open Governance (OG) paradigm and compare and contrast OG with existing governance paradigms. Based on illustrative real-life cases, we will argue that we need a new paradigm that is better capable of explaining these emerging innovative forms of governing cities. We will argue that this requires an understanding of governance as a platform that facilitates an urban ecosystem. By connecting new insights from studies on digital governance to the debate about governance paradigms, this paper results in a set crucial empirical and normative questions about governance of cities and also in guidelines for urban governance that builds upon the rich, emerging interactions in cities that are facilitated by new technologies.